Transglutaminase-modified whey protein/nanocrystalline cellulose composite films: glycerol plasticization optimization and cheese packaging application - Wei Gong; Tao Zhang; Fang Qian; Guangqing Mu; Shujuan Jiang (Carbohydrate Polymer Technologies and Applications, 2025)
To overcome the limitation of bio-based packaging films in terms of mechanical/ barrier properties and preservation of freshness in high-fat foods. This study explored the effect of glycerol content (40 %, 45 %, 50 %, 55 % and 60 %) on the properties of whey protein concentration (WPC) and nanocrystalline cellulose (NCC) composite films and evaluated the effect of transglutaminase (TGase)-modified WPC-based versus commercial polyethylene films (PE film) on the freshness of cheese. The results showed that the WPC-NCC composite film exhibited superior mechanical and barrier properties at a glycerol content of 45 % in comparison to other concentrations. The tensile strength (TS) and elongation at break (EAB) of the WPC-NCC composite film were 1.89 MPa and 26.4 %, respectively, and the water vapor permeability (WVP) reached 3.29 × 10−12 gmPa−1s−1m−2. Structure analysis revealed that the ordered structure of proteins decreases with the increase of glycerol content, and the α-helix content decreased from 11.19 % to 7.1 %. WPC-NCC-TG film was comparable to PE film for cheese preservation within 30 days of storage. The WPC-NCC-TG film effectively inhibited lipid oxidation, delayed the decline of pH, and color deterioration. The WPC-NCC film was modified by TGase provided theoretical and technical support for the development of high-performance bio-based cheese packaging films.